Migrating Foreign Body Bronchus - K.C., A; Sinha, BK; Guragain, R (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 23-24 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6801